2013
DOI: 10.1111/gbb.12088
|View full text |Cite
|
Sign up to set email alerts
|

Selection for reluctance to avoid humans during the domestication of mice

Abstract: Many animal species have been domesticated over the course of human history and became tame as a result of domestication. Tameness is a behavioral characteristic with 2 potential components: (1) reluctance to avoid humans and (2) motivation to approach humans. However, the specific behavioral characteristics selected during domestication processes remain to be clarified for many species. To quantify these 2 different components of tameness separately, we established 3 behavioral tests: the ‘active tame’, ‘pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 43 publications
1
61
0
1
Order By: Relevance
“…The realized heritability ( h 2 ) was estimated using the average contacting and heading values for generations G 5 –G 12 for group S2 and for generations G 3 –G 12 for group S1. The estimated h 2 values for contacting in groups S2 and S1 were 0.205 ± 0.1 (SEM) and 0.07 ± 0.045, respectively, suggesting that contacting is heritable, albeit with low heritability in mice, consistent with a previous study 9 . The estimated h 2 values for heading in groups S2 and S1 were 0.393 ± 0.421 and 0.194 ± 0.206, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The realized heritability ( h 2 ) was estimated using the average contacting and heading values for generations G 5 –G 12 for group S2 and for generations G 3 –G 12 for group S1. The estimated h 2 values for contacting in groups S2 and S1 were 0.205 ± 0.1 (SEM) and 0.07 ± 0.045, respectively, suggesting that contacting is heritable, albeit with low heritability in mice, consistent with a previous study 9 . The estimated h 2 values for heading in groups S2 and S1 were 0.393 ± 0.421 and 0.194 ± 0.206, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Regarding tameness, our previous genetic correlation analyses with 17 wild-derived and laboratory strains of mice revealed evidence that when a higher level of passive tame behavior is observed, active tame behavior tends to be high (Goto et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, comparative analyses between wild and domestic mice revealed that the heritable behavioral characteristics, reluctance to avoid humans but not motivation to approach humans, will be the key for domestication of mice (Goto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations